PENGARUH PENGGUNAAN CASE METHOD TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA SMP PADA MATERI POLA BILANGAN - Fitrianti; Gita Ramadani (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
This study examines the effect of the use of the Case Method on junior high school students' understanding of mathematical concepts in the topic of number patterns. The study was conducted at a public junior high school in Batui using a quantitative approach of the Quasi-Experimental Design type. The research sample consisted of two classes: an experimental class treated with the Case Method and a control class taught with the Conventional method. Data analysis was carried out through normality, linearity, homogeneity tests, and Analysis of Covariance (ANACOVA). The results of the study showed that there was a significant difference between the understanding of mathematical concepts of students in the experimental class and the control class, where the results of the normality test were normally distributed with a significant level in the experimental class at pretest 0.25 and posttest 0.31 which means > 0.05 and the control class at pretest 0.62 and posttest 0.60 which means > 0.05, while the results of the linearity test in the experimental class 0.76 and the control class 0.31 which means > significant level 0.05 and the results of the homogeneity test with a significant level in the pretest of the experimental and control classes 0.89 > 0.05 and in the posttest of the experimental and control classes 0.20 > 0.05. While the value with the ANACOVA test showed H0 was rejected with a significant level of 0.00 ˂ 0.05 which means there is an influence of the case method learning model on the ability to understand the concept, besides that it can also be seen from the results of the mean case method learning model 77.869 and the mean concept understanding 53.38. Thus, it can be concluded that the use of the Case Method has a positive and significant effect on improving students' understanding of mathematical concepts in the material on number patterns.